Drivers of parasite community structure in fishes of the continental shelf of the Western Mediterranean: the importance of host phylogeny and autecological traits. Issue 9 (August 2019) - Carrassón, Maite; Dallarés, Sara; Cartes, Joan E.; Constenla, Maria; Pérez-del-Olmo, Ana; Zucca, Leda; Kostadinova, Aneta
Graphical abstract: Highlights: Drivers of parasite community diversity and structure were assessed in Mediterranean fishes. An original dataset for parasites, preys, environmental and host trait data was developed. Wide variations in richness, abundance and similarity were due to a strong phylogenetic component. Host specificity is a key determinant of community similarity. Host species or higher level taxonomy is the best predictor of parasite richness and abundance. Abstract: We explored the relationships between features of host species and their environment, and the diversity, composition and structure of parasite faunas and communities using a large taxonomically consistent dataset of host-parasite associations and host-prey associations, and original environmental and host trait data (diet, trophic level, population density and habitat depth vagility) for the most abundant demersal fish species off the Catalonian coast of the Western Mediterranean. Altogether 98 species/taxa belonging to seven major parasite groups were recovered in 683 fish belonging to 10 species from seven families and four orders. Our analyses revealed that (i) the parasite fauna of the region is rich and dominated by digeneans; (ii) the host parasite faunas and communities exhibited wide variations in richness, abundance and similarity due to a strong phylogenetic component; (iii) the levels of host sharing were low and involved host generalists and larval parasites; (iv) the multivariate similarity pattern of prey samples showed significant associations with hosts and host trophic guilds; (v) prey compositional similarity was not associated with the similarity of trophically transmitted parasite assemblages; and (vi) phylogeny and fish autecological traits were the best predictors of parasite community metrics in the host-parasite system studied.